Experimental comparison of various quantum key distribution protocols under reference frame rotation and fluctuation - Yoon, Juhwan; Pramanik, Tanumoy; Park, Byung Kwon; Cho, Young Wook; Lee, Sang Yun; Kim, Sangin; Han, Sang Wook; Moon, Sung; Kim, Yong Su (Optics Communications, 2019)
In free-space quantum key distribution (QKD) between moving parties, e.g., free-space QKD via satellite, the reference frame rotation and fluctuation degrades the performance of QKD. Reference-frame-independent QKD (RFI-QKD) provides a simple but efficient way to overcome this problem. While there has been a number of theoretical and experimental studies on RFI-QKD, the experimental verification of the robustness of RFI-QKD over other QKD protocols under the reference frame rotation and fluctuation is still missing. Here, we have constructed a free-space QKD system which can implement BB84, six-state, and RFI-QKD protocols, and compared their performances under the reference frame rotation and fluctuation. With the theoretical analysis and experimental results, we have successfully verified the robustness of RFI-QKD protocol over other QKD protocols in the presence of reference frame rotation and fluctuation.
Keywords: Experimental comparison; Experimental verification; Free spaces; Quantum key distribution protocols; Reference frame; Still missing; Quantum communication; Quantum key distribution; Reference frame rotation and fluctuation